Model Study for Outdoor Data Transmission Performance - Abel Yu Hao, Chai; Yi Lung, Then; Fei Siang, Tay; Hieng Tiong, Su; Natalie Chen Yi, Lim; Chamath Kanalaka, Vithanawasam (2022)
Network performance for outdoor transmissions are varies according to different environment especially when there was obstacle along the transmission path and therefore the expected performance for outdoor transmissions is unpredictable. These unpredictable performances of outdoor data transmission forced Internet Service Providers (ISPs) to use stronger or better routers to establish the data transmission link. So, the initial investment for the project in a rural area will be higher than urban area due to long-range outdoor transmissions. Normally, this cost will be absorbed by the customers, who will be paying higher subscription fees. But, the income of residents in rural areas is lower than urban areas and the ISP is forced to absorb the extra initial investment by prolonging the projects’ breakeven point. Therefore, this study aimed to a model for estimating average data speed for outdoor Wi-Fi data transmission. The average data speed of outdoor Wi-Fi data transmission was modelled by conducting experiments that simulate real-world wireless transmission. The experiments were conducted by selecting suitable transmitter and receivers. The obstacle used in the experiment was made from aluminum plate which has high attenuation for wireless signals. The experimental data were further validated with actual testing with real-world obstacles. The average percentage error for the outdoor Wi-Fi average data speed model was 24.97%.